Temporal artery biopsy in giant cell arteritis: clinical perspectives and histological patterns - Stamatis, Pavlos; Turesson, Carl; Mohammad, Aladdin J. (Frontiers in Medicine, 2024)
Although its role has been debated, temporal artery biopsy (TAB) remains the gold standard for the diagnosis of cranial giant cell arteritis (GCA). The specificity of TAB is excellent and the sensitivity, albeit lower, is comparable with other diagnostic modalities used for the diagnosis of GCA. This outpatient procedure has a low rate of complications and is well integrated in the majority of healthcare systems. The length of the specimen, the number of the examined sections and the prolonged use of glucocorticoids before the biopsy may affect the outcome of the TAB as diagnostic tool. The typical histological findings in GCA are often characterized by granulomatous inflammation with infiltration of mononuclear cells with or without the presence of giant cell, varying degrees of external and internal elastic lamina damage and intimal thickening. Overlooking signs of inflammation in the adventitia and in connective tissue surrounding the temporal artery may lead to false negative results. The distinction between healed arteritis and age-related atherosclerosis may be challenging.